From Canal Horizons to A+: Canal+’s conception of African cinema as a means to conquer the African market? - (:unkn) unknown (My University, 2017)
Not so long ago, the term 'African cinema' evoked the idea of a small number of mostly low-budget auteur films with very limited circulation via international film festivals. They were standardly financed by foreign producers, often with the support of European national funding programmes like Fonds Sud, international agencies like Francophonie or via funds associated with international film festivals (Rotterdam, Venice, Goteborg, etc.). Over the last 20 years a low-cost film industry has developed in Nigeria, launching a trend that has spread across the continent. These small, often artisanal film industries provide national markets with locally-produced images that reach much wider audiences than before thanks to new digital platforms for disseminating them and the proliferation of portable media for watching them. Canal+ has been trying to penetrate the African market since Canal Horizons (1990-2001), although with mixed results. Its new initiatives aim at tapping into the development of local creative talents, this time with the aim of selling African content to local markets in order to compensate for a declining market in France. On March 2, 2017, at the Fespaco in Ouagadougou, Canal+ organized a workshop which presented their new enterprise, Canal+ Afrique, to African filmmakers. On this occasion they presented their team and their expectations in terms of the production of films and television series aimed at the African market. Drawing on (1) interviews with the agents of the redeployment of Canal+ strategy in Africa and with African filmmakers, (2) promotional materials, (3) an analysis of the relationships of force for the supply of the African market with audio-visual productions, we will examine the political, economic and cultural issues raised by films and tv series made for Canal+. Films are a relatively minor part of Canal+’s range of audiovisual products, featuring news, sports programs and entertainment, so it is interesting to con
Keywords: African Research